Non-disclosure of developmental neurotoxicity studies obstructs the safety assessment of pesticides in the European Union - Axel Mie; Christina Rudén (Environmental Health, 2023)
Abstract Background In the European Union (EU), the safety assessment of plant protection products relies to a large extent on toxicity studies commissioned by the companies producing them. By law, all performed studies must be included in the dossier submitted to authorities when applying for approval or renewal of the active substance. Methods For one type of toxicity, i.e. developmental neurotoxicity (DNT), we evaluated if studies submitted to the U.S. Environmental Protection Agency (EPA) had also been disclosed to EU authorities. Results We identified 35 DNT studies submitted to the U.S. EPA and with the corresponding EU dossiers available. Of these, 9 DNT studies (26%) were not disclosed by the pesticide company to EU authorities. For 7 of these studies, we have identified an actual or potential regulatory impact. Conclusions We conclude that (1) non-disclosure of DNT studies to EU authorities, in spite of clear legal requirements, seems to be a recurring phenomenon, (2) the non-disclosure may introduce a bias in the regulatory risk assessment, and (3) without full access to all performed toxicity studies, there can be no reliable safety evaluation of pesticides by EU authorities. We suggest that EU authorities should cross-check their data sets with their counterparts in other jurisdictions. In addition, applications for pesticide approval should be cross-checked against lists of studies performed at test facilities operating under Good Laboratory Practice (GLP), to ensure that all studies have been submitted to authorities. Furthermore, rules should be amended so that future studies should be commissioned by authorities rather than companies. This ensures the authorities’ knowledge of existing studies and prevents the economic interest of the company from influencing the design, performance, reporting and dissemination of studies. The rules or practices should also be revised to ensure that non-disclosure of toxicity studies carries a significant legal risk for pesticide companies.